Precarity on Stage: the Creative and Political Dimensions of Affect in Ceresoli’s Theatre Production La Merda - Jansen, Monica (FRAME, Journal of Literary Studies, 2026)
The theatre monologue The Shit / La Merda won several prizes. This play on humiliation and anger can be linked to precarity in various ways. Firstly, the woman’s narrative on her proximate television audition reveals how socioeconomic precarity in Italy conditions young people and females in particular. The play unravels the fallacy of post-feminist emancipation. Secondly, the piece also exemplifies Italian mobility and the “trans-national.” Thirdly, the female’s “subjectivation” to the neoliberal logic is not only a humiliating experience but also a potential for resistance. It cannot be thought separately from the “cruel optimism” of the good-life fantasy. Finally, affect also functions as cultural activism within the context of Teatro Valle Occupato.